WooW-II: Workshop on open workflows - Arribas-Bel, Daniel; de Graaff, Thomas (Region (Louvain-la-Neuve), 2015)
This resource describes WooW-II, a two-day workshop on open workflows for quantitative social scientists. The workshop is broken down in five main parts, where each of them typically consists of an introductionary tutorial and a hands-on assignment. The specific tools discussed in this workshop are Markdown, Pandoc, Git, Github, R, and Rstudio, but the theoretical approach applies to a wider range of tools (e.g., LATEX and Python). By the end of the workshop, participants should be able to reproduce a paper of their own and make it available in an open form applying the concepts and tools introduced.